Has technology fostered access to capital for small and medium sized enterprises? - Stellato Neto, Douglas (2020)
When evaluating small businesses constraints to growth, it may be possible to understand the extent that banks could offer better credit conditions to enterprises that use information and communication technologies (ICTs) more extensively. The role of ICTs has become more strategic in improving competitiveness of small and medium-sized enterprises (SMEs), plus there are several obstacles that prevent SME implementation of ICTs. Given the low rates of economic growth and high poverty rates in the East African region, and in despite of growth rates that have recently improved there low levels of development make the case for considering how to accelerate investment levels. The objective of our study is to investigate the impact of ICTs on access to capital. We will use access to technology licensed from a foreign company and owning and using a website as proxies for ICTs. The study uses data gathered from the World Bank Enterprise Surveys. We expect access to ICTs to have a positive effect on SME access to capital. Our findings suggest that there is a positive association between access to ICTs and access to capital. The effects of the use of technology from a foreign firm over credit granting are verified in our empirical analysis, and so are the use of a website with a positive correlation. The correlation of the use of technology from a foreign firm over the loan granted was found to be of some statistical significant, referencing to its importance to the firms’ operations, and we also found correlations when assessing the use of a website by firms, further detailed in the empirical analysis.